MAPPING SYSTEM FOR LOCATION OF STUNTING CASES IN TODDLER IN TANJUNG BALAI CITY USING WEBGIS - Alfa, Zikri; Yusda, Riki Andri; Rahayu, Elly (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2024)
Abstract: Data on stunting cases among toddlers in Datuk Bandar Timur sub-district, Tanjung Balai city Not yet processed in a way computerized use digital map , so that the monitoring process in-depth investigation of the distribution and patterns of stunting in a area Not yet presented with Good . This matter Of course impact on cadre Public health center Semula Jadi For monitor number nutrition bad And spread prevalence of stunting in Datuk Bandar Timur sub-district, Tanjung Balai city . For That need development A system internal data management form chart nor map that can be give description spread nutrition bad in the region Mayor. Planning And development system information This done with use method data collection and interview direct to the UPTD Community Health Center Semula Jadi . Objective it was built this webgis can assist in identifying areas that need nutritional intervention, mapping the prevalence of stunting and malnutrition, as well as monitoring nutrition programs and optimizing resource allocation. Results from GIS can plays an important role in supporting efforts to prevent and overcome stunting problems by providing tools effective software for collecting, analyzing and visualizing nutritional data spatially. The use of web GIS can also provide information on stunting locations from UPTD Semula Jadi Health Center data.Keywords : geographic information system; location mapping system; stunting.  Abstrak: Data kasus stunting pada balita di kecamatan datuk bandar timur kota tanjung balai belum diproses secara terkomputerisasi menggunakan peta digital, sehingga proses pemantauan penyelidikan mendalam tentang sebaran dan pola stunting disuatu daerah belum tersajikan dengan baik. Hal ini tentu berdampak pada kader puskesmas Semula Jadi untuk memantau angka gizi buruk dan penyebaran prevalensi stunting di kecamatan datuk bandar timur kota tanjung balai. untuk itu perlu pembangunan sebuah sistem pengelolaan data dalam bentuk grafik maupun peta yang dapat memberikan gambaran penyebaran gizi buruk diwilayah Datuk Bandar. Perancangan dan pembangunan sistem informasi ini dilakukan dengan menggunakan metode pengambilan data dan wawancara langsung ke UPTD Puskesmas Semula Jadi. Tujuan dibangunnya webgis ini dapat membantu dalam identifikasi daerah yang membutuhkan intervensi gizi, pemetaan prevalensi stunting dan gizi buruk, serta memantau program-program gizi dan optimalisasi alokasi sumber daya. Hasil dari SIG dapat berperan penting dalam mendukung upaya pencegahan dan penanggulangan masalah stunting dengan menyediakan alat software yang efektif untuk pengumpulan, analisis, dan visualisasi data gizi secara spasial. Kegunaan webgis juga dapat memberikan informasi mengenai lokasi stunting dari data UPTD Puskesmas Semula Jadi.Kata kunci: sistem informasi geografis; sistem pemetaan lokasi; stunting